Extreme learning machine based speaker recognition - Hu, Zongjiang. (2011)
Speaker Recognition is the process of automatically recognizing who is speaking based on the individual information included in speech waves. Speaker Recognition is basically classified into speaker identification and speaker verification. It can be used in many fields such as banking by telephone, voice dialling, voice mail, and security control for secret information areas.